93.5k views
1 vote
A student performed the following steps to solve the equation.

2x - (x - 2) = x+3
2x - x + 2 = x+3
x + 2 = x+3
*+2 - x= x+3 - X
2 = 3
Move words to the blanks to complete the sentence.
The equation has
solutions because the equation 2 = 3 is
true.
zero
Infinitely many
always
never

2 Answers

2 votes

Answer:

the answer is zero,false

User Masroore
by
4.8k points
7 votes

9514 1404 393

Answer:

zero, false

Explanation:

The equation has zero solutions because the equation 2=3 is false.

__

There are no values of the variables that will make that equation true, hence no solutions.

User Toozyfuzzy
by
4.6k points